The People with Asperger syndrome and anxiety disorders (PAsSA) trial: a pilot multicentre, single-blind randomised trial of group cognitive–behavioural therapy. Issue 2 (March 2016) - Langdon, Peter E.; Murphy, Glynis H.; Shepstone, Lee; Wilson, Edward C.F.; Fowler, David; Heavens, David; Russell, Alexandra; Rose, Alice; Malovic, Aida; Mullineaux, Louise
Abstract : Background: There is a growing interest in using cognitive–behavioural therapy (CBT) with people who have Asperger syndrome and comorbid mental health problems. Aims: To examine whether modified group CBT for clinically significant anxiety in an Asperger syndrome population is feasible and likely to be efficacious. Method: Using a randomised assessor-blind trial, 52 individuals with Asperger syndrome were randomised into a treatment arm or a waiting-list control arm. After 24 weeks, those in the waiting-list control arm received treatment, while those initially randomised to treatment were followed up for 24 weeks. Results: The conversion rate for this trial was high (1.6:1), while attrition was 13%. After 24 weeks, there was no significant difference between those randomised to the treatment arm compared with those randomised to the waiting-list control arm on the primary outcome measure, the Hamilton Rating Scale for Anxiety. Conclusions: Trials of psychological therapies with this population are feasible. Larger definitive trials are now needed.